Study On Innovation And Challenges Of Teachers In Using AI In Islamic Religious Education Learning - Ahmad Nanda Maulana; Teguh Pamuji; Miftah Falah Udwi Syarfiah; Fatih Nur Alif Ramadhan Korlin; Sarbini Sarbini; Saca Suhendi (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study aims to analyze teacher innovation and challenges in utilizing Artificial Intelligence (AI) in Islamic Religious Education (PAI) learning. Using a library research approach, this study examines various credible scientific sources to build a comprehensive understanding of AI integration in PAI learning. The findings indicate that AI supports personalized learning through data analysis and recognition of student learning patterns, expands access to learning resources in various formats, and creates interactive learning experiences through simulations and visualizations. Innovations in AI utilization include self-directed learning, Quranic learning applications with voice recognition features, educational chatbots, virtual assistants, and Augmented Reality and Virtual Reality technologies that enrich learning experiences. However, the implementation of AI also presents several challenges, such as limited infrastructure and technology access, potential reduction of humanistic interaction between teachers and students, and excessive dependence on technology. Therefore, AI should be positioned as a strategic partner for teachers rather than a replacement, maintaining a balance between technological innovation and the spiritual essence of religious education. A wise and well-directed integration of AI is expected to strengthen the quality of PAI learning in responding to the dynamics of the digital era.